Improving and fine-tuning the properties of peptide-based hydrogels via incorporation of peptide nucleic acids. Issue 38 (28th September 2020) - Giraud, Tristan; Bouguet-Bonnet, Sabine; Marchal, Philippe; Pickaert, Guillaume; Averlant-Petit, Marie-Christine; Stefan, Loic
Abstract : Incorporation of peptide nucleic acids into peptide sequences provides new opportunities to improve and fine-tune peptide self-assembly properties. Abstract : Peptide self-assemblies have attracted intense research interest over the last few decades thanks to their implications in key biological processes ( e.g., amyloid formation) and their use in biotechnological and (bio)material fields. In particular, peptide-based hydrogels have been highly considered as high potential supramolecular materials in the biomedical domain and open new horizons in terms of applications. To further understand their self-assembly mechanisms and to optimize their properties, several strategies have been proposed with the modification of the constituting amino acid chains via, per se, the introduction of d -amino acids, halogenated amino acids, pseudopeptide bonds, or other chemical moieties. In this context, we report herein on the incorporation of DNA-nucleobases into their peptide nucleic acid (PNA) forms to develop a new series of hybrid nucleopeptides. Thus, depending on the nature of the nucleobase ( i.e., thymine, cytosine, adenine or guanine), the physicochemical and mechanical properties of the resulting hydrogels can be significantly improved and fine-tuned with, for instance, drastic enhancements of both the gel stiffness (up to 70-fold) and the gel resistance to external stress (up to 40-fold), and the generation of both thermo-reversible and uncommon red-edge excitation shift (REES) properties. To decipher the actual role of each PNA moiety in the self-assembly processes, the induced modifications from the molecular to the macroscopic scales are studied thanks to the multiscale approach based on a large panel of analytical techniques ( i.e., rheology, NMR relaxometry, TEM, thioflavin T assays, FTIR, CD, fluorescence, NMR chemical shift index). Thus, such a strategy provides new opportunities to adapt and fit hydrogel properties to the intended ones and pushes back the limits of supramolecular materials.